Perception Of Generation X And Millennials Towards Tax Compliance In Indonesia - Pohan, Fawwaz Muhammad Zakli; Marfiana, Andri (Educoretax, 2024)
Digitalization of taxation such as DGT Online is one of the programs from DGT to be able to assist taxpayers in fulfilling compliance properly. In addition, Industrial Revolution 4.0 and Tax Administration 3.0 have almost the same principles as the DGT's tax digitalization program. Apart from the digital side, there is a public trust factor that can affect compliance. The results of this study obtained a conclusion that, the application of tax digitalization in terms of services, especially system convenience and supervision, has not been very effective in increasing tax compliance. This is seen from generation X and millennials. Other factors such as law enforcement and sanctions are prominent. Public trust in DGT's performance has been a consideration for taxpayers to remain tax compliant. The integrity value issued by the DGT is a guide for the community to comply with taxes. In addition, generational perspectives on compliance are generally similar, they remain tax compliant because they are aware of the effects of sanctions. What makes the difference is their response to corruption cases, where the millennial generation is more open and assertive than generation X.